Anti-diabetic potential assessment of aqueous and ethanol extracts of arrow poison (Strophanthus hispidus) plant stem bark in Wistar male rats - M Osibemhe; M Ibrahim; I.O. Onoagbe (Journal of Applied Sciences and Environmental Management)
Diabetes mellitus is a chronic disease, for which there is no known cure except in some specific situation. The available orthodox drugs used for its management are having disadvantages. The aim of this study is to evaluate the anti-diabetic potential of aqueous and ethanol extracts of Strophanthus hispidus (SH) stem bark in Wistar male rats. Diabetes mellitus was induced by intraperitoneal injection of streptozotocin (55 mg/kg). Blood glucose concentrations, serum α-amylase and lipid profile of normal and diabetic rats were monitored for 12 weeks. The rats were treated with 250 mg/kg of aqueous and ethanol extracts of Strophanthus hispidus respectively. Dose-response study was also carried out. The results revealed significant (P<0.05) progressive decrease in fasting blood glucose concentration on the 2nd-12th weeks and 4th-12th weeks in normal and diabetic-treated rats respectively. Total cholesterol, LDL and TG levels were lowered significantly (P<0.05) by the extracts in normal and diabetic treated rats, whereas HDL levels (17.6±0.50 mg/dl) (aqueous) and (21.4±1.28 mg/dl) (ethanol) were elevated in diabetic treated rats. The activity of serum α-amylase was also elevated by the extract in diabetic treated rats. These findings indicated that SH showed hypoglycemic, anti-hyperlipidemic and anti-diabetic activities. These findings may be connected with the presence and amount of phytochemicals in the plant.